LOCAL LANGUAGE MAINTENANCE IN TRANSLATING ENGLISH TEXT - Havid Ardi (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2018)
Translation and foreign language mostly influence the use of local language di Indonesia. However, in the translation text entitled "Asal-Usul Elite Minangkabau Modern: Respons terhadap Kolonial Belanda Abad XIX/XX," there is an attempt to maintain a local language, Minangkabau. The original text was written in English by E. Grave an American researcher. This paper aims to identify translation techniques as the form of language maintenance and its impact on the readability of the translation text. The findings show that adaptation, established equivalence, particularization, explicitation, and addition techniques are used in maintaining Minangkabaunese. The assessment of the translation indicates that these techniques did not decrease the level of readability. The readability level is at an easy level with a score of 3.53. This finding implies that language maintenance does not reduce the readability of translation and it is a positive effort that translators can make.